2015
DOI: 10.1136/bmjopen-2014-007324
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Framingham general cardiovascular risk score in a multiethnic Asian population: a retrospective cohort study

Abstract: ObjectiveThis study aims to examine the validity of the Framingham general cardiovascular disease (CVD) risk chart in a primary care setting.DesignThis is a 10-year retrospective cohort study.SettingA primary care clinic in a teaching hospital in Malaysia.Participants967 patients’ records were randomly selected from patients who were attending follow-up in the clinic.Main outcome measuresBaseline demographic data, history of diabetes and smoking, blood pressure (BP), and serum lipids were captured from patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 22 publications
6
67
1
2
Order By: Relevance
“…FRS was a scoring system made by traditional cardiovascular risk factors to predict the ten-year probability of coronary heart disease, which was considered a suitable tool for Asia population but may be overestimated cardiovascular risk of women among Taiwanese [35]. Results of this study showed insignificant association between dominant handgrip strength and FRS, which was in line with the previous report [36].…”
Section: Discussionsupporting
confidence: 87%
“…FRS was a scoring system made by traditional cardiovascular risk factors to predict the ten-year probability of coronary heart disease, which was considered a suitable tool for Asia population but may be overestimated cardiovascular risk of women among Taiwanese [35]. Results of this study showed insignificant association between dominant handgrip strength and FRS, which was in line with the previous report [36].…”
Section: Discussionsupporting
confidence: 87%
“…This study was conducted at an outpatient primary care clinic at the University Malaya Medical Centre, a teaching hospital in the Klang Valley of Kuala Lumpur, Malaysia. All patients aged more than 30 years at baseline (1998), without any cardiovascular event at baseline, were eligible for the study . One thousand four hundred sixty‐four subjects were randomly selected from patients registered with the clinic, using a computer‐generated number based on patients' clinic registration number.…”
Section: Methodsmentioning
confidence: 99%
“…The risk score included age, total cholesterol, high-density lipoprotein, systolic and diastolic blood pressure, diabetes and smoking [17, 18]. The score is previously validated in a multiethnic Asian population [19, 20]. …”
Section: Variablesmentioning
confidence: 99%